Engineering Bifunctional Catalytic Microenvironments for Durable and High-Energy-Density Metal–Air Batteries - Nsanzimana, Jean Marie Vianney; Cai, Lebin; Jiang, Zhongqing; Xia, Bao Yu; Maiyalagan, Thandavarayan (Nano-Micro Letters, 2025)
Rechargeable metal–air batteries have gained significant interest due to their high energy density and environmental benignity. However, these batteries face significant challenges, particularly related to the air-breathing electrode, resulting in poor cycle life, low efficiency, and catalyst degradation. Developing a robust bifunctional electrocatalyst remains difficult, as oxygen electrocatalysis involves sluggish kinetics and follows different reaction pathways, often requiring distinct active sites. Consequently, the poorly understood mechanisms and irreversible surface reconstruction in the catalyst’s microenvironment, such as atomic modulation, nano-/microscale, and surface interfaces, lead to accelerated degradation during charge and discharge cycles. Overcoming these barriers requires advancements in the development and understanding of bifunctional electrocatalysts. In this review, the critical components of metal–air batteries, the associated challenges, and the current engineering approaches to address these issues are discussed. Additionally, the mechanisms of oxygen electrocatalysis on the air electrodes are examined, along with insights into how chemical characteristics of materials influence these mechanisms. Furthermore, recent advances in bifunctional electrocatalysts are highlighted, with an emphasis on the synthesis strategies, microenvironmental modulations, and stabilized systems demonstrating efficient performance, particularly zinc– and lithium–air batteries. Finally, perspectives and future research directions are provided for designing efficient and durable bifunctional electrocatalysts for metal–air batteries. Highlights: 1 Overview of metal–air batteries architecture, reaction mechanisms, and challenges in developing bifunctional air-breathing electrodes. 2 Comprehensive discussion on engineering the microenvironment chemistry of noble metal-free bifunctional oxygen electrocatalysts. 3 Insights into future research directions for earth-abundant bifunctional catalysts with enhanced performance and durability, aiming to guide the future development of advanced bifunctional catalysts for scalable applications.